Aroma classification and flavor characterization of Streptococcus thermophilus fermented milk by HS-GC-IMS and HS-SPME-GC-TOF/MS. (October 2022) - Liu, Ao; Zhang, Hongwei; Liu, Tongjie; Gong, Pimin; Wang, Yawei; Wang, Hongze; Tian, Xiaoying; Liu, Qiqi; Cui, Qingyu; Xie, Xiang; Zhang, Lanwei; Yi, Huaxi
Abstract: 46 Streptococcus thermophilus strains, isolated from commercial starters cultures, were studied. The aroma of the fermented milk by these strains was evaluated by quantitative descriptive analysis (QDA). According to its major sensory attribute, the fermented milks were classified into milky-type, creamy-type, cheesy-type, fermented-type and miscellaneous-type groups. One representative sample of each group was analyzed by headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS) and headspace-solid phase microextraction-gas chromatography-time-of-flight mass spectrometry (HS-SPME-GC-TOF/MS) to describe their volatile compositions. 48 and 72 volatile compounds were identified, respectively. The fingerprint analysis showed that each aroma type had specific volatile compounds. Six important differential volatile compounds including 2, 3-butanedione, 2, 3-pentanedione, 2-undecanone, octanoic acid, hexanoic acid and 2-hydroxy-3-pentanone were selected as key compounds by principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA), which allowed to discriminate the specific aroma types. These key compounds could be used as indicators to develop fermented milks with specific aroma and flavor features. Graphical abstract: Image 1 Highlights: 46 fermented milk samples by S. Thermophilus were divided into 5 aroma types. GC-IMS and GC-TOF/MS were used to establish the flavor fingerprints of different aroma types. 6 key compounds of different aroma types were screened out by multivariate statistical analysis.